2017
DOI: 10.1111/ane.12727
|View full text |Cite
|
Sign up to set email alerts
|

Triptan use in Australia 1997-2015: A pharmacoepidemiological study

Abstract: The use of triptan derivatives in Australia per head of population for treating migraine attacks continued to increase over the 18-year period studied, with use of recently introduced derivatives more than substituting for decreased use of older triptans. This suggests that the available treatments of migraine attacks had achieved what were considered less than adequate therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A similar strategy was used by another Italian study [26] based on electronic health records of general practitioners and obtaining results comparable to ours. Moreover, to date, several studies used healthcare databases to investigate the use of triptans, both concerning Italian settings [27, 28] and other countries, such as France, the Netherlands, Germany and Australia [2932]. Nevertheless, no epidemiological data were derived from these data sources on the real-life UMN in migraine, which represents an important issue in the neurological field.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy was used by another Italian study [26] based on electronic health records of general practitioners and obtaining results comparable to ours. Moreover, to date, several studies used healthcare databases to investigate the use of triptans, both concerning Italian settings [27, 28] and other countries, such as France, the Netherlands, Germany and Australia [2932]. Nevertheless, no epidemiological data were derived from these data sources on the real-life UMN in migraine, which represents an important issue in the neurological field.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian pharmacoepidemiological study showed that total triptan use has increased at an average annual rate of 112% over the 18-year period. 22 Besides, only a minority of migraine patients use the specific antimigraine drug triptans (10% in Denmark, 17% in Italy, and 35% in France). 23 25 The most probable reason is the relatively low efficacy.…”
Section: Current Acute Treatmentsmentioning
confidence: 99%
“…The debate revolved around safety, efficacy, consistency, drugdrug interactions with prophylactic drugs, pharmacokinetics/ pharmacodynamics, new delivery pathways, extension of this pharmacological class to the population aged under 18 or over 65 years, evaluation of common adverse events, disability levels [6][7][8][9][10][11][12]. Notwithstanding, only 27% of migraine patients receive a correct diagnosis and only 17% of them takes triptans for a crisis [13,14]. Therefore, two different studies in Italy and Australia show how in a real population of migraine patients only the great minority of them receive a correct advice for the treatment of the crisis [13,14].…”
Section: Travelling From Nsaids To Triptans To Cgrpmentioning
confidence: 99%
“…Notwithstanding, only 27% of migraine patients receive a correct diagnosis and only 17% of them takes triptans for a crisis [13,14]. Therefore, two different studies in Italy and Australia show how in a real population of migraine patients only the great minority of them receive a correct advice for the treatment of the crisis [13,14].…”
Section: Travelling From Nsaids To Triptans To Cgrpmentioning
confidence: 99%
See 1 more Smart Citation